The text of Acts of the Apostles in the writings of Origen - Helton, Stanley N. (Studia Patristica Supplement, 2022)
The purpose of this study is to ascertain the textual identity of the text of 'Acts' as used by Origen (ca. 185-254 CE). The research includes an analysis and evaluation of Origen's citations of and allusions to 'Acts', with that information providing the basis for reconstructing and analyzing Origen's text of 'Acts', and thereby locating his text of 'Acts' within the history of the transmission of the New Testament. The working hypothesis at the outset of this research is that Origen's text of 'Acts' should be most akin to the text of 'Acts' found in MS 1739 with perhaps some intermittent Western readings and a few Byzantine readings. The assumptions of previous scholars suggest this hypothesis. The results of this research, to the contrary, show that Origen's text of 'Acts' is most akin to Codex Vaticanus (B03), following closely other Primary Alexandrian MSS, with no distinct Western readings, but in some cases, Origen shows knowledge of readings that reappear in some later secondary Alexandrian and Byzantine MSS of 'Acts'.